The Effect of Therapeutic Alliance on Dropout in Cognitive Processing Therapy for Posttraumatic Stress Disorder. Issue 4 (27th March 2021) - Sijercic, Iris; Liebman, Rachel E.; Stirman, Shannon Wiltsey; Monson, Candice M.
Abstract: A substantial number of individuals who undergo cognitive processing therapy (CPT) for posttraumatic stress disorder (PTSD) drop out before receiving a full course of treatment. Therapeutic alliance, defined as the working relationship between the therapist and client, is a dynamic process within therapy that may change over time. Research suggests that therapeutic alliance is associated with dropout in various treatments. However, no studies have yet examined the association between therapeutic alliance and dropout in CPT, and few studies have examined therapeutic alliance longitudinally over the course of treatment. Examining alliance in CPT through different methods may increase clinicians' understanding of how to tailor interventions to prevent treatment dropout. The present study examined the association between therapeutic alliance and treatment dropout among 169 participants in a randomized implementation effectiveness trial. In total, 33.1% of clients dropped out over the course of CPT, and nearly half of these individuals dropped out during the first six sessions. Continuous‐time survival analysis results indicated that mean ratings of alliance significantly predicted treatment dropout, Wald χ 2 (1, N = 167) = 4.08, Exp(β) = .64, p = .043, whereas initial alliance, late alliance, and change in alliance over treatment did not. These findings suggest that overall therapeutic alliance is an important predictor of dropout from CPT. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Traditional Chinese 治療聯盟對創傷後壓力症認知加工治療中途退出的影響 摘要 大量接受認知處理療法(CPT)治療創傷後壓力症(PTSD)的人在接受整個療程之前就退出了。治療聯盟被定義為治療師和客戶之間的工作關係, 是治療中的一個動態過程, 可能會隨著時間而改變。研究表明, 治療聯盟與各種治療的退出有關。然而, 目前還沒有研究對認知處理療法中治療聯盟和退出的關係進行研究, 也很少有研究對治療過程中的治療聯盟進行縱向研究。通過不同的方法對認知處理療法中的聯盟進行研究, 可以增加臨床醫生對如何調整干預措施以防止退出的理解。本研究在一個隨機實施的有效性試驗中, 考察了169名參與者的治療聯盟和治療退出之間的關係。在認知處理療法的過程中, 總共有33.1%的客戶退出, 其中近一半的人在前六次治療中退出。連續時間的生存分析結果表明, 聯盟的平均評分顯著地預測了治療的退出, Wald χ2(1, N = 167) = 4.08, Exp(β) = .64, p = .043, 而初始聯盟、後期聯盟和治療中聯盟的變化則沒有。這些發現表明, 整體治療聯盟是預測認知處理療法退出的一個重要因素。 Simplified Chinese 治疗联盟对创伤后压力症认知加工治疗中途退出的影响 摘要 大量接受认知处理疗法(CPT)治疗创伤后压力症(PTSD)的人在接受整个疗程之前就退出了。治疗联盟被定义为治疗师和客户之间的工作关系, 是治疗中的一个动态过程, 可能会随着时间而改变。研究表明, 治疗联盟与各种治疗的退出有关。然而, 目前还没有研究对认知处理疗法中治疗联盟和退出的关系进行研究, 也很少有研究对治疗过程中的治疗联盟进行纵向研究。通过不同的方法对认知处理疗法中的联盟进行研究, 可以增加临床医生对如何调整干预措施以防止退出的理解。本研究在一个随机实施的有效性试验中, 考察了169名参与者的治疗联盟和治疗退出之间的关系。在认知处理疗法的过程中, 总共有33.1%的客户退出, 其中近一半的人在前六次治疗中退出。连续时间的生存分析结果表明, 联盟的平均评分显著地预测了治疗的退出, Wald χ2(1, N = 167) = 4.08, Exp(β) = .64, p = .043, 而初始联盟、后期联盟和治疗中联盟的变化则没有。这些发现表明, 整体治疗联盟是预测认知处理疗法退出的一个重要因素。